Peran Strategis Pemuda dalam Mendorong Tata Kelola Pariwisata Berkelanjutan: Sebuah Studi Partisipasi Publik dalam Perspektif Administrasi Publik - Arifin, Solthan Nur; Atika, Dewie Brima; Karmilasari, Vina (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
This research aims to explore the strategic role of youth in promoting sustainable tourism governance in Indonesia, focusing on the perspectives of public administration and public participation. Youth, as agents of change, have significant potential to contribute to the management of tourism resources; however, they are often marginalized in the decision- making process. Through a qualitative approach and scoping review method, this research identifies the forms and levels of youth participation in tourism governance, as well as the factors that support and hinder their involvement. The findings indicate that youth participation can be categorized into three areas: participation in planning, implementation, and evaluation of tourism programs. Supporting factors such as government policy support, access to information, and the presence of active youth organizations play a crucial role in enhancing participation. Conversely, barriers such as lack of support, cultural stigma, and limited access to resources can diminish youth motivation to engage. Recommended strategies to strengthen the role of youth include the development of relevant educational and training programs, strengthening youth organizations as collaborative platforms, and utilizing technology and social media for tourism promotion. By actively involving youth in decision- making processes and providing access to resources, it is expected that their engagement in sustainable and inclusive tourism management will be encouraged, resulting in positive impacts for local communities.